Workshop on the Writing of Scientific Articles and Grant Proposals for Lecturers to Increase Opportunities for Research Funding and the Publication of Scientific Work - Hamidah, Jamiatul; Ariyani, Herda; Rafiek, Muhammad (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
A workshop was conducted on research grant proposals and community service to enhance the quality of research and publications by lecturers at Universitas Muhammadiyah Banjarmasin. The primary objective of this workshop is to provide novice lecturers with the opportunity to acquire grants and increase the number of national and international publications. Service Learning is implemented in this workshop through both online and offline workshops. During the offline workshop, participants were provided with explanations regarding strategies for obtaining research and community service grants. Online participants received assistance in the composition of reputable journal articles, which included the following steps: writing according to templates, submitting, and revising. Twenty individuals participated in this workshop. The workshop conclusion is the impact and benefits for lecturers at Universitas Muhammadiyah Banjarmasin, specifically the enhanced skill of all participants in the composition of journal articles and grant proposals. The results showed that five participants completed the standard NLR grant, and one completed the community service grant organized by the Directorate General of Higher Education, Research, and Technology (DGHERT).